2020
DOI: 10.1002/ejp.1553
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pain perceptual biases related to fear of pain and threat in a pain‐free sample

Abstract: Background The association between fear of pain (FOP) and pain intensity has remained unclear. This study aimed to examine whether highly pain‐fearful participants showed pain perceptual biases to general painful stimulus or to specific threatening painful stimulus. Methods Fifty‐nine undergraduates were recruited into low (n = 30) and high (n = 29) FOP groups and completed a threatening pain perception task with two tasks. Task 1 assessed pain perceptual biases by calculating the percentage of near‐threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…3,13 "Şiddetli ağrı korkusu" (1,3,5,6,9,10,13,18,25,27. maddeler), "hafif ağrı korkusu" (2,4,7,12,19,22,23,24,28,30. maddeler) ve "tıbbi ağrı korkusu" (8,11,14,15,16,17,20,21,26,29.…”
Section: Hasta Bi̇lgi̇ Formumentioning
confidence: 99%
“…3,13 "Şiddetli ağrı korkusu" (1,3,5,6,9,10,13,18,25,27. maddeler), "hafif ağrı korkusu" (2,4,7,12,19,22,23,24,28,30. maddeler) ve "tıbbi ağrı korkusu" (8,11,14,15,16,17,20,21,26,29.…”
Section: Hasta Bi̇lgi̇ Formumentioning
confidence: 99%
“…Yang and Bateer [20] recruited 59 university students to receive painful stimuli in the dorsum of the left hand via two electrodes and looked at self-reported measures (Fear of Pain Questionnaire, Anxiety Sensitivity Index, STAI-T) in relation to their pain experience [20]. The researchers concluded that high fear of pain groups reported higher pain intensity in conjunction with higher anxiety levels when compared to the low fear of pain groups.…”
Section: Personality and Pain Correlationmentioning
confidence: 99%
“…The researchers concluded that high fear of pain groups reported higher pain intensity in conjunction with higher anxiety levels when compared to the low fear of pain groups. The authors found that threat appraisal of pain played an important role in the association between pain-related fear and pain perceptual biases [20].…”
Section: Personality and Pain Correlationmentioning
confidence: 99%
“…Personal traits such as being fearful of the anticipation or the experience of pain may account for interindividual differences in reporting or perceiving pain 11 . Picture a parent faced with the task of taking their child to the dentist for a major dental procedure.…”
Section: Introductionmentioning
confidence: 99%